2021
DOI: 10.1038/s41392-020-00441-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional hair follicle regeneration: an updated review

Abstract: The hair follicle (HF) is a highly conserved sensory organ associated with the immune response against pathogens, thermoregulation, sebum production, angiogenesis, neurogenesis and wound healing. Although recent advances in lineage-tracing techniques and the ability to profile gene expression in small populations of cells have increased the understanding of how stem cells operate during hair growth and regeneration, the construction of functional follicles with cycling activity is still a great challenge for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 148 publications
0
92
0
1
Order By: Relevance
“…Hence, the activation and stability of the hair regeneration cycle are key factors in achieving an intact HF. However, HF loss is often accompanied by the termination and/or dysregulation of the hair regeneration cycle, such as a shortened anagen phase or a failed transition from the telogen to anagen phase ( Ji et al, 2021). The activity of HFSCs and DPCs is the main driving force for the continuous hair regeneration cycle and is regulated by various signaling molecules (Rahmani et al, 2014;Chen et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the activation and stability of the hair regeneration cycle are key factors in achieving an intact HF. However, HF loss is often accompanied by the termination and/or dysregulation of the hair regeneration cycle, such as a shortened anagen phase or a failed transition from the telogen to anagen phase ( Ji et al, 2021). The activity of HFSCs and DPCs is the main driving force for the continuous hair regeneration cycle and is regulated by various signaling molecules (Rahmani et al, 2014;Chen et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…During hair regeneration, HFSCs proliferate and differentiate into HF components, and DPCs, which are now considered a reservoir of multipotent stem cells, regulate HF development and growth (Rahmani et al, 2014;Ji et al, 2021). HFSCs and DPCs undergo rapid proliferation to fuel the initial stage of hair growth that supports the prolonged growth of the hair (Rahmani et al, 2014;Ji et al, 2021). Based on the inhibited hair regeneration observed in the Fpr2 KO mice, we examined the activation of HFSCs and DPCs by assessing the specific activation markers for each cell type.…”
Section: Deletion Of Fpr2 Decreases Activation Of Hair Follicle Stem Cells (Hfscs) and Dermal Papilla Cells (Dpcs)mentioning
confidence: 99%
“…Hair loss is a significant concern of human disorder regardless of age and gender. This can be attributed to aging, environmental reasons, stress, or the lack of hair follicle recovery due to poor tissue regeneration of injured tissues ( 88 ). Hair follicle is an ectodermal organ composed of two main parts, including the epithelium of keratinocytes and the mesenchyme of dermal papilla (DP) cells ( 89 ).…”
Section: Hair Follicle Regenerationmentioning
confidence: 99%
“…All hair follicles periodically undergo a hair cycle that consists of anagen (growth), catagen (regression) and telogen (rest) ( Ji et al, 2021 ). Many recent studies have reported that hair cycle is regulated by the interaction between mesenchymal cells and epithelial cells in hair follicles, and the proliferation of dermal papilla (DP) cells by the activation of PI3K/Akt/Wnt/β-catenin pathway may be the key factor ( Botchkarev and Kishimoto, 2003 ; Kang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%